2022
DOI: 10.3390/cells11223640
|View full text |Cite
|
Sign up to set email alerts
|

The Predicted Splicing Variant c.11+5G>A in RPE65 Leads to a Reduction in mRNA Expression in a Cell-Specific Manner

Abstract: Pathogenic variants in RPE65 lead to retinal diseases, causing a vision impairment. In this work, we investigated the pathomechanism behind the frequent RPE65 variant, c.11+5G>A. Previous in silico predictions classified this change as a splice variant. Our prediction using novel software’s suggested a 124-nt exon elongation containing a premature stop codon. This elongation was validated using midigenes-based approaches. Similar results were observed in patient-derived induced pluripotent stem cells (iPSC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The c.11+5G>A variant has been described multiple times as pathogenic in various worldwide populations; however, there were no more data on its prevalence among other alterations in the RPE65 gene [22,37,40]. A study by Vázquez-Domínguez I. et al shows that the c.11+5G>A variant does not affect splicing as expected according to prediction programs, but leads to a significant decrease in the expression of RPE65, specific for the pigment epithelium, with an undetermined mechanism [41].…”
Section: Discussionmentioning
confidence: 99%
“…The c.11+5G>A variant has been described multiple times as pathogenic in various worldwide populations; however, there were no more data on its prevalence among other alterations in the RPE65 gene [22,37,40]. A study by Vázquez-Domínguez I. et al shows that the c.11+5G>A variant does not affect splicing as expected according to prediction programs, but leads to a significant decrease in the expression of RPE65, specific for the pigment epithelium, with an undetermined mechanism [41].…”
Section: Discussionmentioning
confidence: 99%
“…The RPE65 :c.11+5G>A variant has been observed in at least five probands in the homozygous state and in at least 27 probands in the heterozygous state together with another RPE65 pathogenic variant in the literature (Supplementary Table 3). A recent study applied the midigene approach and found that the variant produces a minor mRNA species with a 124-nt intron retention and a majority of mRNA from normal splicing 10 . Interestingly, RPE65 mRNA and protein levels are markedly diminished in patient-derived retinal pigment epithelial (RPE) cells, which was not rescued by inhibition of nonsense-mediated decay, leading to the conclusion that the variant causes diminished RPE65 expression independent of splicing 10 .…”
Section: Online Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted November 3, 2023. ; https://doi.org/10.1101/2023.11.02.23297963 doi: medRxiv preprint intron retention and a majority of mRNA from normal splicing 10 . Interestingly, RPE65 mRNA and protein levels are markedly diminished in patient-derived retinal pigment epithelial (RPE) cells, which was not rescued by inhibition of nonsense-mediated decay, leading to the conclusion that the variant causes diminished RPE65 expression independent of splicing 10 .…”
Section: Online Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some studies have highlighted inconsistencies between splicing aberrations detected using midigenes or simpler cellular models, as opposed to more sophisticated models derived from reprogrammed induced pluripotent stem cells, such as photoreceptor precursor cells or retinal organoids. As the genomic context of the complex models closely resembles that of the native retinal environment, these are more representative of the actual splicing process in the retina ( 29 , 32 , 39 , 40 ). These findings point to the limits imposed by the midigene system.…”
Section: Discussionmentioning
confidence: 99%